A critical review of natural gas emissions certification in the United States. (1st February 2023) - Garg, Sankalp; Boz, Deniz Ege; Gilbert, Ben; Crompton, Jim
Abstract: Concerns about the climate and local air impacts of emissions from the oil and gas supply chain have caused a reevaluation of natural gas' role in a low carbon future. In response, some producers, large purchasers, and investors have pushed to certify some gas deliveries as 'responsibly-sourced' or 'green', which could give rise to a differentiated gas market. Third-party oil and gas certifications have been under development for several years, however, their focus has historically been on a broader set of societal impacts and risks, and they have typically focused on the upstream sector. Recent advances have been focused on methane emissions and supply chains into the certification process. In this paper we provide a critical review of several prominent natural gas certification processes. We do so within a broader historical context of using third-party market certifications and labels to differentiate clean vs. dirty versions of commodities.